Estudio de factibilidad para la creación de una empresa comercializadora de confecciones y accesorios bordados para dama en la ciudad de Pereira departamento de Risaralda (2014)
The purpose of this project is to conduct a feasibility study for the creation of a marketer of apparel and accessories for women embroidery through an outlet located in the city of Pereira, Risaralda. This project was written for students from “Universidad del Quindío” Armenia, Quindío, Colombia, to obtain the title of “Administración de Negocios”. It aims to encourage the creation of new ideas company Business to activate the regional and national economy. Research showed that the source of the problem was from 1998 to date; finding that nationwide there are approximately 350,000 people directly linked to the artisanal sector as artisans, representing 15% of employment in the manufacturing sector; 1,200,000 people are also involved in the sector indirectly either as temporary dedicated craftsmen, trade, or as service development and other aspects of the craft agents. This favored national employment policies and generate new jobs Colombian artisans. The Feasibility Study identifies opportunities and threats taking into account relevant aspects such as the market in both the demand and supply. On demand we will satisfy the tastes and preferences of consumers and embroidered apparel accessories, for the wide variety of products and good service at the point of sale. And supply will come from the north of department “Valle del Cauca, Colombia” where are organized a production system of apparel and accessories that are embroidered under competitive technique works. According to the marketing study conducted by means of 203 surveys, was found that the target market consists of 120,168 women in level 3, 4 and 5 were obtained as being a more inexpensive product selective and they have purchasing power, even though the product is for these three level the marketing study found that demand for it is high since it is represented by 274357 women for the year 2014.